A novel extraperitoneal approach exploration for the treatment of urachal mass: a retrospective observational single-center study. Issue 1 (28th October 2022) - Sui, Yuanming; Zhang, Zongliang; Zhao, Kai; Zhang, Yulian; Wang, Zhenlin; Zhu, Guanqun; Yang, Han; Li, Xueyu; Wang, Qinglei; Yin, Xinbao; Wang, Ke
Abstract : Background: To explore the extraperitoneal laparoscopic urachal mass excision technique and its safety and efficacy in treating urachal mass. Methods: Baseline characteristics were collected from patients who underwent surgery to diagnose a urachal cyst or abscess in our hospital between January 2020 and August 2021. The full-length of the urachus and part of the top bladder wall were completely removed through the extraperitoneal approach. Patient outcomes were collected to evaluate surgical safety and efficacy, including operation time, intraoperative blood loss, drainage tube removal time, length of stay (LOS), and postoperative complications. Results: All 20 surgeries were successfully performed laparoscopically, and no case was converted to open surgery. The mean body mass index of the patients was 24.6 ± 2.2. The mean patient age was 49.3 ± 8.7 years. The mean size of the cysts was 3.0 ± 0.4 cm. The mean operation time was 56.3 ± 12.0 min. The mean intraoperative blood loss was 28.0 ± 6.4 mL. The mean drainage tube removal time was 3.0 ± 0.5 days. The mean LOS was 5.2 ± 0.4 days. The mean follow-up was 13.4 ± 2.1 months. No postoperative complications were observed during the follow-up period. The short-term follow-up and small patient cohort limited our outcome evaluation. Conclusion: Our results indicated that the extraperitoneal laparoscopic approach was a safe and effective method to treat urachal mass. Given the limitations of the study, further multiple and larger sample-sized trials are required to confirm our findings.